2011
DOI: 10.1016/j.ab.2010.11.038
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput fluorescence polarization assay to identify inhibitors of Cbl(TKB)–protein tyrosine kinase interactions

Abstract: The Casitas-B-lineage Lymphoma (Cbl) proteins play an important role in regulating signal transduction pathways by functioning as E3-ubiquitin ligases. The Cbl proteins contain a conserved tyrosine kinase binding (TKB) domain that bind over a dozen proteins, including protein tyrosine kinases (PTKs) in a phosphorylation dependent manner. The cell surface expression levels of the PTKs are regulated by Cbl-mediated ubiquitination, internalization, and degradation. Dysfunction in this signaling cascade has result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Based on this, Kumar et al . are developing strategies to identify small molecules or peptides that bind the Cbl TKB and block interaction with the RTK (53, 54). The efficacy of such an approach remains to be tested.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Based on this, Kumar et al . are developing strategies to identify small molecules or peptides that bind the Cbl TKB and block interaction with the RTK (53, 54). The efficacy of such an approach remains to be tested.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…We recently reported the development and miniaturization of a Cbl(TKB) FP assay for high throughput screening to identify Cbl(TKB) inhibitors. 29 Here, the FP assay was adapted to quantify binding of 12-mer peptide or pentapeptide to Cbl(TKB) and inhibition of binding by various peptides. Peptides 1 and 2 were labeled with a fluorophore at the N-terminus to generate two probes ( 3, Flu-pYTPEP and 4, Flu-TLNSDGpYTPEPA) for the FP assay.…”
mentioning
confidence: 99%
“…We, and others, have shown that the phophotyrosine is a key binding component as the non-phosphorylated Tyr-containing peptide does not bind Cbl(TKB). 6, 7, 29 Analysis of the 33G values relative to 1 reveals that each residue modestly contributes to Cbl(TKB) binding (Figure 3A, cyan bars). Interestingly, there is a significant loss of activity in 19 , suggesting that the proline residue at the P+4 position makes substantial contribution to binding.…”
mentioning
confidence: 99%
“…Ces données suggèrent que l'on peut cibler l'interaction entre c-Cbl et les RTK pour favoriser la différenciation ostéoblastique des CSM, ce qui ouvre une nouvelle voie thérapeutique potentielle pour favoriser l'ostéogenèse et la répara-tion osseuse ( Figure 3A). L'utilisation de molécules pharmacologiques capables d'inhiber de façon spécifique l'interaction entre c-Cbl et les RTK, molécules actuellement en développement [26,27], pourrait ainsi permettre de promouvoir la différenciation ostéogénique des cellules souches mésenchymateuses in vivo. E3.…”
Section: Rôle Des Protéines Cbl Dans L'ostéogenèseunclassified